Experimental Analysis of a Self-Homogenization of the Fuel Spray in the 3d-Pm Engine - Rejus Kumar, Arun V; Francis Britto, A. Sagai (International Journal of Psychosocial Rehabilitation, 2019)
The advantages of homogeneous combustion in internal combustion (I.C.) engines are well known and many research groups all over the world are working on its practical realization. Recently, the present authors have proposed a new combustion concept that fulfils all requirements to perform homogeneous combustion in I.C. engines using the Porous Medium Combustion Engine, called “PM -engine”. This is an I.C. engine with the following processes realized in a porous medium: internal heat recuperation, fuel injection and vaporization, mixing with air, homogenization, 3 Dthermal self-ignition followed by a homogeneous combustion. Figure 1 shows the simplest case of the operation of a PM-engine, where the PM-combustion chamber is mounted in engine head. During the intake stroke it is weak influence of the PM-heat capacitor on the in-cylinder air thermodynamic conditions. Heat exchange process (nonadiabatic compression) increases with continuing compression, and at the TDC the whole combustion air is closed in the PM volume. Near the TDC of compression the fuel is injected in to PM volume and very fast fuel vaporization and mixing with air occur in 3D-structure of PM-engine. The selfignition process and homogeneous combustion occur in PM volume close to the TDC